Years of Life and Productivity Loss due to Adult Sudden Unexpected Death in the United States - Mirzaei, Mojtaba (Med Care, 2019)
BACKGROUND: Few studies have evaluated the years of life lost (YLL) and productivity loss due to Sudden Unexpected Death (SUD). The burden of SUD on society is undetermined due to lack of population- based studies and comprehensive adjudication methods. OBJECTIVE: We estimated YLL and productivity loss from SUD in working age adults and compared it with leading causes of death in the United States. METHODS: We screened all out of hospital deaths among people 20–64 in Wake County, North Carolina from 2013 to 2015 to adjudicate SUDs. We extrapolated Wake County incidence to estimate the age and sex standardized rate of SUD in the United States. YLL was calculated based on the remaining life expectancy of the victims. Incorporating market and housekeeping value estimated the present value of lifetime productivity loss due to SUD. RESULTS: SUD incidence rates in the US adults 20–64 were 49.3 (95%CI: 41.2–58.3) and 21.7 (95%CI: 16.5–27.8) per 100000 among men and women, respectively. SUD resulted in the loss of 2 million years of life, accounting for 10.0% of YLL from all causes of death. Among natural causes of death, YLL from SUD was only lower than that from all cancers combined and heart disease. Lifetime productivity loss due to SUD was about $51 billion, exceeding productivity loss from any individual cancer. CONCLUSION: Sudden unexpected death is an important source of YLL and productivity loss among adults 20–64. Such high burden on society justifies prioritizing health policies and interventions toward preventing sudden unexpected death.